Biohydrogen production from cheese whey powder by Enterobacter asburiae: Effect of operating conditions on hydrogen yield and chemometric study of the fermentative metabolites - Cecilia L. Alvarez-Guzmán; Sergio Cisneros-de la Cueva; Victor E. Balderas-Hernández; Adam Smoliński; Antonio De León-Rodríguez (Energy Reports, 2020)
In this study, the response surface methodology (RSM) with a central composite design (CCD) was applied to evaluate the effect of temperature, initial pH and cheese whey powder concentration (CWP) on the hydrogen yield and hydrogen production rate by the Enterobacter asburiae. Batch fermentations were performed in 120 cm3 serological bottles with a working volume of 110 cm3. The CWP concentration evaluated was in a range of 4.8-55.2 g dm-3, initial pH in a range of 3.4-10.1 and temperatures of 4.8-55.2~°C. The maximum hydrogen yield and production rate of 1.19~±~0.01 mol H2 mol-1 lactose and 9.34~±~0.22 cm3 dm-3 h-1, respectively were achieved at the optimum conditions of 25.6~°C, initial pH of 7.2 and 23.0 g dm-3 CWP. Moreover, a chemometric analysis was applied for the comparison and visualization of the effect of the different operating conditions on the distribution of the metabolites produced. According to the hierarchical clustering analysis (HCA), the production of acetic acid, formic acid and ethanol was stimulated mainly by low temperature conditions of 15~°C, while the production of reduced compounds such as succinic acid, lactic acid and 2,3-butanediol was favored by 30~°C, initial pH 6.8 and CWP concentrations Ï 30 g dm-3.
Keywords: 330; Agro-industrial wastes; Chemometrics; Dark fermentation; Hydrogen; RSM